Adsorption characteristics and mechanism of Cd by mealworm frass - Hae-Been Kim; Jae-Hoon Lee; Ye-Ji Lee; Jun-Suk Rho; Jeong-Min Lee; Seong-Heon Kim; Jong-Hwan Park; Dong-Cheol Seo (Applied Biological Chemistry)
Abstract This experiment was conducted to evaluate the adsorption–desorption characteristics and mechanisms of heavy metals by the mealworm frass (MF). The adsorption characteristics of Cd by MF were predominantly influenced by initial pH, MF dosage, temperature, and reaction time. The maximum adsorption capacity of Cd by MF was 48.1 mg/g, which was well described by Langmuir isotherm and pseudo-second-order models. The optimal desorption solution for separating Cd from Cd-adsorbed MF was 0.02 M HCl, which showed a high desorption efficiency of over 90%. In particular, the adsorption mechanism of Cd by MF was confirmed through functional group change, cation exchange, precipitation experiment, and it was found that Cd was predominantly affected by cation exchange and precipitation on the MF surface. The amounts of Cd fractionated by F1 (exchangeable) and F2 (bonded to carbonate) solutions were 58.9 and 25.2% of the total fractionated Cd amount, which means that Cd adsorbed by MF can be easily eluted/mobilized by environmental changes. Considering the above results, it is believed that MF can be used as an effective adsorbent to remove Cd. However, since the adsorption of Cd by MF is sensitive to environmental changes and the bond itself is weak, it is considered that a special management plan is needed.